Strategi Dakwah Forum Komunikasi Masjid Cibuntu dalam Meningkatkan Wawasan Keagamaan Bagi Kalangan Remaja di Kampung Cibuntu Sukabumi - M. Alby Fauzi; Malki Ahmad Nasir; Muhammad Fauzi Arif (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. The purpose of this study was to determine the da'wah strategy of the Communication Forum Cibuntu Mosque (FKMC) in increasing religious insight for teenagers in Cibuntu Sukabumi Village. This research uses qualitative type with descriptive method. Data collection techniques were carried out through observation, interviews and documentation. The results showed that FKMC's da'wah strategy in increasing religious insight for teenagers in Cibuntu Village was carried out by compiling a program of religious activities and a personal approach to visit each house, and to invite active participation in every religious activity. The FKMC program consists of routine recitation among teenagers, visiting the mosques in the Cibuntu Village area, and bahsul masail. Supporting factors for FKMC in improving religious knowledge among teenagers are supported by the Indonesian Ulama Council at the sub-district level, asatidz and asatidzah, and community leaders in Cibuntu Village. The factors that hinder FKMC including the differences in understanding among FKMC members while the lack of teenagers in participating in religious activities are awareness. Abstrak. Tujuan penelitian ini untuk mengetahui strategi dakwah Forum Komunikasi Masjid Cibuntu (FKMC) dalam meningkatkan wawasan keagamaan bagi kalangan remaja di Kampung Cibuntu Sukabumi. Penelitian ini menggunakan jenis kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa strategi dakwah FKMC dalam meningkatkan wawasan keagamaan bagi kalangan remaja di Kampung Cibuntu dilakukan dengan menyusun program kegiatan keagamaan dan pendekatan secara personal dengan mengunjungi setiap rumah untuk mengajak aktif dalam setiap kegiatan keagamaan. Program FKMC terdiri dari pengajian rutin kalangan remaja, kunjungan pengajian ke Mushola di wilayah Kampung Cibuntu, dan bahsul masail. Faktor pendukung FKMC dalam meningkatkan wawasan keagamaan bagi kalangan remaja karena adanya dukungan Majelis Ulama Indonesia tingkat kecamatan, para asatidz dan asatidzah, serta tokoh masyarakat Kampung Cibuntu. Faktor penghambat meliputi perbedaan pemahaman antar anggota FKMC serta kurangnya kesadaran di kalangan remaja untuk ikut serta dalam kegiatan keagamaan.